Liver fibrosis prevalence and risk factors in patients with psoriasis: A systematic review and meta-analysis - Yongpisarn, Tanat; Namasondhi, Amornrut; Iamsumang, Wimolsiri; Rattanakaemakorn, Ploysyne; Suchonwanit, Poonkiat (Frontiers in Medicine, 2022)
Background Patients with psoriasis are more likely than matched controls in the general population to have advanced liver fibrosis; however, our understanding of these patients is limited. There is currently no systematic evaluation of the prevalence and risk factors of liver fibrosis in psoriasis patients. Objective To evaluate the prevalence of psoriasis patients who are at high or low risk for advanced liver fibrosis and determine the risk factors for developing liver fibrosis. Methods Electronic searches were conducted using the PubMed, Embase, Scopus, and Cochrane Library databases from the dates of their inception till May 2022, using the PubMed, Embase, Scopus, and Cochrane Library databases. Any observational study describing the prevalence and/or risk factors for liver fibrosis in patients with psoriasis was included. Results Patients with psoriasis at high risk for advanced liver fibrosis had a pooled prevalence of 9.66% [95% confidence interval (CI): 6.92–12.75%, I2 = 76.34%], whereas patients at low risk for advanced liver fibrosis had a pooled prevalence of 77.79% (95% CI: 73.23–82.05%, I2 = 85.72%). Studies that recruited methotrexate (MTX)-naïve patients found a lower prevalence of advanced liver fibrosis (4.44, 95% CI: 1.17–9.22%, I2 = 59.34%) than those that recruited MTX-user cohorts (12.25, 95% CI: 6.02–20.08%, I2 = 82.34%). Age, sex, BMI, PASI score, psoriasis duration, MTX cumulative dose, and the prevalence of obesity, MTX users, diabetes mellitus, hypertension, dyslipidemia, and metabolic syndrome were not identified as sources of heterogeneity by meta-regression analysis. The pooled odds ratios for age >50 years, BMI > 30, diabetes mellitus, hypertension, dyslipidemia, and metabolic syndrome were 2.20 (95% CI: 1.42–3.40, I2 = 0%), 3.67 (95% CI: 2.37–5.68, I2 = 48.8%), 6.23 (95% CI: 4.39–8.84, I2 = 42.4%), 2.82 (95% CI: 1.68–4.74, I2 = 0%), 3.08 (95% CI: 1.90–4.98, I2 = 0%), and 5.98 (95% CI: 3.63–9.83, I2 = 17%), respectively. Conclusion Approximately 10% of the population with psoriasis is at high risk for advanced liver fibrosis, while 78% are at low risk. Patients over the age of 50 with obesity, diabetes, hypertension, dyslipidemia, and/or metabolic syndrome have an increased risk of developing liver fibrosis, necessitating monitoring. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022303886], identifier [CRD42022303886].